A longitudinal examination of peritraumatic emotional responses and their association with posttraumatic stress disorder and major depressive disorder among veterans. Issue 5 (20th October 2017) - Engel-Rebitzer, Eden; Bovin, Michelle J.; Black, Shimrit K.; Rosen, Raymond C.; Keane, Terence M.; Marx, Brian P.
ABSTRACT: Research has revealed a significant association between several peritraumatic emotional responses and posttraumatic stress disorder (PTSD). Preliminary research has also linked peritraumatic emotional responses with a diagnosis of major depressive disorder (MDD). The majority of this research has been cross-sectional, thereby making it difficult to determine the extent to which the various peritraumatic emotional responses may increase risk for, or serve as a premorbid marker of, PTSD and MDD. This study examined the longitudinal role of peritraumatic emotional responses on the subsequent development of PTSD and MDD in a sample of US military veterans. Whereas a number of peritraumatic emotional responses were concurrently associated with PTSD, only peritraumatic numbness maintained the association with this diagnosis longitudinally. For MDD, peritraumatic numbness was the only emotional response related to the diagnosis both concurrently and longitudinally. Study findings are a preliminary proof of concept that peritraumatic numbness may serve as a premorbid marker for the development of PTSD and MDD following a traumatic event. Implications of these findings for the diagnosis, assessment, and treatment of both PTSD and MDD are discussed.